Lifelong learning in tourism and sospitality: Breakthrough European and Asian Experience - Rodionova E. V. Elena Viktorovna; Agranovich V. B. Viktoriya Borisovna; Konyukhova T. V. Tatiana Vasilievna; Biryukov D. K. Dmitry Konstantinovich; Melnikova V. G. Valentina Grigorjevna (2017, 2017)
Title screen